The Model of National Education at Higher Pedagogical School, Its Application into Practice - Dirgėlienė, Indrė (Acta Paedagogica Vilnensia, 2001)
The article discloses the model of preparing for future teacher's profession, also the main principles and structure of this model, its possibilities applying into practice, training future teacher's national self-consciousness, developing the features of personality. This is according to the natural pedagogic experiments, material of research, implemented at Klaipėda Higher Pedagogical School (in the years 1990-1997). The problem of the research: nationality cultivation preparing the future teachers. The aim of research: to decide the meaning of the national training model of personality features extension and national self-consciousness for future teachers. The object of research: students’ national training in at Higher Pedagogical School. The selection of the research object selection was settled by applying the nature of professional studies in Higher Pedagogical School, that includes suitable conditions for conforming to formal and additional non-formal training, and for putting into practice the national principle.
Keywords: Pedagogical school; teacher education; future teacher; nationality; national education.